Unmasking Multiple Myeloma: The Importance of Suspecting Malignancy in Atypical Chronic Pain Mimicking Degenerative Conditions—A Case Report - Bi Mo; Sandra Sacks; Jerry Markar (Clinical Case Reports)
ABSTRACT Heightened clinical vigilance for multiple myeloma is essential in patients presenting with atypical chronic pain progression. Symptoms may overlap with degenerative musculoskeletal conditions, frequently leading to misdiagnosis. This underscores the necessity of a thorough evaluation when symptoms are refractory to conventional therapies, in order to facilitate timely diagnosis and effective management of malignancy.